STUDI KUALITAS DAN PENGOLAHAN AIR SUMUR POMPA TANGAN DENGAN PEMANFAATAN ABU SEKAM DI DESA JALAN LURUS KABUPATEN HULU SUNGAI UTARA - Febrianto Rahman; Darni Subari; Lusita Wardhani; Efansyah Noor (Universitas Lambung Mangkurat, 2012)
The clean water that being used by the people in Hulu Sungai Utara Regency is low until the year of 2008, which is 53.5%, even nationally, is still under the target that being expected. The target that being expected by the urban that use clean water is 80% from all citizen, and 60% for the rural (Health Service of HSU Regency, 2009). The clean water distribution is to even out, there is still a cluster family there’s not get clean water. One of the villages is Jalan Lurus Village Sungai Pandan Districts. Where the peoples are very depend on the use of well hand pump refinery to supply their life. Even so, the well hand pump that being used by the peoples are had complaint, it’s because the water is causing yellow tarnish on white cloth, and also cause scab on cooker that made from metal. This is caused by the iron rate that very highly on that well hand pump. The purpose of this research is to knowing the feasibility of well hand pump (SPT) as a water to drink or only as clean water; knowing the water quality parameters like physic concentration (turbidity), chemistry (pH, Fe and Manganese), and bacteriologist (E-Coli). The first data on this research is ten sample that had taken from the well hand pump have the highly iron rate equal to 2.9150 mg/l, pH equal to 6.27, the highly Manganese rate equal to 0.1204 mg/l. The highest pH is happen on B2A4 treatment (combination of 20 gram ash rice with 8 hours immersion time is 8.62); the lowest pH rate is happen on B1A1 treatment (combination of 5 gram ash rice with 4 hours immersion time is 7,60). The decrease of highest Fe mean is happen on B2A4 treatment (combination of 20 gram ash rice with 8 hours immersion time with Fe rate 0.90 mg/l) and the decrease of lowest Fe mean is happen on B1A1 treatment (combination of 5 gram ash rice with 4 hours with Fe rate 1.62 mg/l). Manganese rate with combination treatment of ash rice concentration 5 gram, 10 gram, 15 gram and 20 gram in 4 and 8 hours immersion, so after the treatment is being doing proceeds all the Manganese rate become 0 mg/lt.. The turbidity mean up after the ash rice is being given on each concentration and immersion time. The higher escalation of turbidity mean happen on B1A4 treatment, because this A4 (20 gram) treatment has the highest concentration ash rice dan the immersion time only 4 hours (B1). Based on the Health Minister Adjudication 907 year 2002, the well hand pump (SPT) in Jalan Lurus Village Sungai Pandan District Hulu Sungai Utara Regency is not on the criteria as a drink water but only as a clean water. Ash rice with concentration variety treatment and immersion time maximally can reduce the Fe and Mn rate and also can increase the water pH of SPT so can fullfil the drink water qualification. Ash rice can increase the need for drink water but also need particular treatment. E-Coli amount does not effect the treatment so need to be coked (240mpn/100 ml).